Synthesis of 2‐Arylbenzoselenazoles from Se‐mediated Redox Condensation of 2‐Chloronitrobenzene and Arylmethyl Chloride. Issue 15 (17th April 2020) - Gan, Haifeng; Cao, Mengru; Wu, Hongli
Abstract: A selenium‐mediated redox condensation of 2‐chloronitrobenzene and arylmethyl chloride to obtain 2‐arylbenzoselenazoles has been realized under metal‐free condition. The reactions proceeded in moderate‐to‐good yields with good functional compatibility and gram‐scale achievement. Primarily mechanistic investigation suggested that key intermediate Bn(Se)nBn II, was first isolated and confirmed by NMR. Abstract : A selenium‐mediated redox condensation of 2‐chloronitrobenzene and arylmethyl chloride to obtain 2‐arylbenzoselenazoles has been realized under metal‐free condition. The reactions proceeded in moderate‐to‐good yields with good functional compatibility and gram‐scale achievement. Primarily mechanistic investigation suggested that key intermediate Bn(Se)n Bn II, was first isolated and confirmed by NMR. This methodology provides a complementary method for the efficient construction of 2‐arylbenzoselenazole